Prediction of the Corrosion Inhibition Efficiency of Imidazole Derivatives: A Quantum Chemical Study - Saprizal Hadisaputra; Zohrul Iskandar; Dina Asnawati (Acta Chimica Asiana, 2019)
Corrosion is a process of metal destruction due to the metal-acidic environment reaction. The uncontrolled corrosion process lead to massive losses. Administering inhibitors of organic compounds on the metal surface may prevent the corrosion processes. Organic inhibitors are low toxicity, environmentally friendly, effective easy to obtain and cheap. The study aims to determine the effect of substituents to the efficiency of corrosion inhibition of imidazole in carbon steel based on quantum chemical parameters. Corrosion inhibition efficiency values ​​are strongly influenced by the addition of substituents namely electron donors (CH3, CHCH2, NH2, CH2OH and OH) and electron withdrawal (CHO, COOH, NO2, F and Cl). The addition of amine group NH2 increased the corrosion inhibition efficiency to 91 % whereas amino group NO2 reduced the efficiency of corrosion inhibition to 64 %. Analysis of the Fukui function shows that imidazole has active sides on the C1 and C3 atoms. NBO analysis shows that there is an interaction of N5 atoms that donate electrons to Fe13 at 8.67 kcal.mol-1. In conclusion, the addition of an electron donor group increases the efficiency of corrosion inhibition of imidazole.